If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -4 = -14 Reorder the terms: -4 + 5t = -14 Solving -4 + 5t = -14 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 5t = -14 + 4 Combine like terms: -4 + 4 = 0 0 + 5t = -14 + 4 5t = -14 + 4 Combine like terms: -14 + 4 = -10 5t = -10 Divide each side by '5'. t = -2 Simplifying t = -2
| (x*2)-9=x | | 8x+12=-6x-18 | | -6(m-23)=1 | | a+b=cfindb | | 8+5v=-8(-8v+8)+v | | 1/7-11=1/4x-14 | | 3.2+2.2x=3x | | x(2x-3)(4x+1)=0 | | 2x^2-2=45 | | -x-4.7=9 | | x/4=4/3 | | c=37+22h | | 12x-y=-10 | | 1/2r=3 | | c=22h+37 | | -36-8n=-3(3n+2)-5n | | f(x)=-3x^2-30x-82 | | 0.2x/x=2.5 | | xsquared-8x=20 | | 40m+0.25=25m+0.45 | | 9(k-2/3)=33=0 | | sinx=0.36736578268 | | (2)/(x^3)=0 | | X-kx+16=0 | | (2)/(x^3) | | 6x+2(100)=4x+40 | | X+x-27+x= | | 8x-(-3x-5)=5-x | | 3e=53 | | 0.4x+12.8=x-2.86 | | x+20y=24 | | K-kx+16=0 |